IHOP_2002: NRL P-3 CNRS Leandre II Data. Version 1.0 - Flamant, C. (UCAR/NCAR - Earth Observing Laboratory, 2005)
This dataset contains CNRS Leandre II data recorded during P-3 flights. The LEANDRE II Water Vapor DIAL system aboard the NRL P-3 was operated during the International H20 Project (IHOP_2002) field experiment from May 19th through June 25th 2002. This dataset contains data from May 22nd through June 19th 2002.
Keywords: Upper Air; Lidar; NRL P-3; Aircraft > > NRL P-3 > Aircraft operated by Naval Research Lab > 02d1826b-a34b-4773-a61d-de91677eb8bd; Differential Absorption Lidar - DIAL; Earth Remote Sensing Instruments > Active Remote Sensing > Profilers/Sounders > Lidar/Laser Sounders > DIAL > Differential Absorption Lidar > bebf8e8d-babf-4f4f-bff3-d04c80bc67dc; Lidar; Earth Remote Sensing Instruments > Active Remote Sensing > Profilers/Sounders > Lidar/Laser Sounders > LIDAR > Light Detection and Ranging > 7166c458-f935-4bd9-a322-d92830cf0c33; Leandre II; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WATER VAPOR > WATER VAPOR PROFILES > WATER VAPOR MIXING RATIO PROFILES; EARTH SCIENCE > SPECTRAL/ENGINEERING > RADAR > RADAR REFLECTIVITY; IHOP_2002; International H2O Project 2002